The Effect of Digital Literacy, Trust in Security, and Transaction Costs on Optimizing the Utilization of QRIS in MSMEs with Ease of Use as an Intervening Variable - Saputra, Avindra Adzandi; Suhardi, Suhardi; Akbar, Jufrisani (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study aims to analyze the influence of digital literacy, trust in security, and transaction costs on optimizing the use of QRIS by MSME actors in Bangka Belitung, with ease of use as a mediation variable. Using an explanatory research type quantitative approach, data was collected through a Likert questionnaire 1–5 from 157 MSME actors selected by purposive sampling. The validity and reliability of the instruments were tested through KMO, Bartlett's Test, and Cronbach's Alpha. The analysis was carried out using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method using SmartPLS, as well as mediation tests through bootstrapping and Sobel tests. The results show that digital literacy has a significant direct effect on QRIS optimization. Meanwhile, trust in security and transaction costs has an indirect effect through the ease of use as a mediator. These findings confirm the importance of the perception of convenience in encouraging the adoption of QRIS by MSMEs. The practical implication is that policy interventions are needed in the form of increasing digital literacy, simplifying features, and cost transparency by the government and digital service providers.